Design multiplex PCR primer and probe gen ORF1ab and gen N on COVID-19 - Amazan, Hasna Mirda; Putra, Andani Eka; Rita, Rauza Sukma (International Journal Of Community Medicine And Public Health, 2023)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus which is a new strain of the Coronavirus, the primary and probe designs were carried out to find candidate primers and probes to be used as the detection of COVID-19. The purpose of this study was to design multiplex PCR on primers and ORF1ab and N gene probes in COVID-19 examination using the multiplex PCR method and it is expected to have good validity in the examination. Methods: The research design is in the form of explorative descriptive with a cross sectional approach. Starting from April to December 2021. The samples used in this study were 221 COVID-19 gene sequences downloaded from the NCBI and GISAID gene databases. Results: The design results of the ORF1ab gene primer and probe with forward primer: 5'- CGCAATTTACAACACAGAC -3' reverse primer: 5'- GTTCTTTATGCTAGCCACT -3' amplicon length 183 bp, and probe sequence: FAM 5'-AAACACACAACAGCATCGTCA-3' BHQ-1, on the N gene with forward primer: 5'-AATTCAACTCCAGGCAG -3' and reverse primer: 5'- CTCTCTCAAGCTGGTTCAATC -3' amplicon length 111 bp, and probe sequence: HEX 5'-CAGCAAAGCAAGAGCAGCA-3' BHQ-1 primary pair sequence and ORF1ab gene probe and N gene conjecture qualified for q-PCR. Conclusions: The obtained primary and probe pair sequences can be used as COVID-19 detection using the multiplex PCR method.